The Ambiguous Impact of Performance Measurement on Service Quality - Tøssebro, Jan; Mjøen, Odd Morten; Bruteig, Rebekka (Frontiers in Rehabilitation Sciences, 2022)
Background: Performance measurement is growing in importance as a management tool in services for disabled people. The aim of this article is to add to the existing literature by exploring a) the motivation for the introduction of such measurements, b) the reasoning behind the choice of current indicators, and c) the impact of performance measurements on service delivery. Methods: 1) A study of documents (national and, if available, also local) on the motivation for, choice of, and implementation of quality measurements, and 2) interviews with top and middle managers in community services for people with intellectual disabilities or mental health difficulties. Results: A varied set of motivations have been identified, including the intention to introduce a more facts-based and transparent governance, the need for information that supports the management of scarce resources, and as a tool in the development of service quality for users. The motivation appears to be dependent on level of government, and the attitude among service unit managers tends to be ambivalent; they want performance measurements but cannot see how to measure the important aspects of service quality. The choice of actual indicators is subject to a process bias; that is, one measures what is easily available in administrative systems. The results concerning impact on services are less clear and also context dependent. We have identified usage in the search for cost-cutting possibilities and defense against critique and found that reporting runs the risk of reinforcing routinization of services. Discussion: The possible impact on service management is discussed. Layers of ambiguity are outlined, as measurements can be tools for quality development and the defense of current services against “unrealistic demands” from the media or stakeholders. The measurements tend to be used more as sources of governance information than tools for quality development. Conclusion: The impact of quality measurement tends to be rather ambiguous. In extreme cases, it functions as a tool for budget control. Conversely, unit managers call for better measurement of user outcomes and expect that such measurement can balance the current preoccupation with input indicators, such as expenditures.